A novel modified-indirect ELISA based on spherical body protein 4 for detecting antibody during acute and long-term infections with diverse Babesia bovis strains. Issue 1 (December 2017) - Chung, Chungwon; Suarez, Carlos; Bandaranayaka-Mudiyanselage, Carey; Bandaranayaka-Mudiyanselage, Chandima-Bandara; Rzepka, Joanna; Heiniger, TJ; Chung, Grace; Lee, Stephen; Adams, Ethan; Yun, Grace; Waldron, Susan
Abstract Background Cattle persistently infected withBabesia bovis are reservoirs for intra- and inter-herd transmission. SinceB. bovis is considered a persistent infection, developing a reliable, high-throughput assay that detects antibody during all stages of the infection could be pivotal for establishing better control protocols. Methods A modified indirect enzyme-linked immunosorbent assay (MI-ELISA) was developed using the spherical body protein-4 (SBP4) ofB. bovis to detect antibody against diverse strains through all infection stages in cattle. This SBP4 MI-ELISA was evaluated for sensitivity and specificity against field sera from regions with endemic and non-endemicB. bovis . Sera were also evaluated from cattle infected experimentally with various doses and strains during acute and persistent infection with parasitemia defined by nested PCR. Results The format variables for SBP4 MI-ELISA were optimized and the cutoff for positive and negative interpretation was determined based on receiver operating characteristic curve analysis usingB. bovis positive and negative sera tested in the reference immunofluorescence assay (IFA). The diagnostic specificity of the SBP4 MI-ELISA using IFA-negative sera collected from Texas was 100%, significantly higher than the cELISA (90.4%) based on an epitope in the rhoptry-associated protein-1 (RAP-1 cELISA). The diagnostic sensitivity of the SBP4 MI-ELISA was 98.7% using the IFA-positive sera collected from several areas of Mexico, in contrast to that of the RAP-1 cELISA at 60% using these same sera. In cattle infected with low and high doses of threeB. bovis strains, the SBP4 MI-ELISA remained antibody positive for 11 months or more after initial detection at 10 to 13 days post-inoculation. However, the RAP-1 cELISA did not reliably detect antibody after eight months post-inoculation despite the fact that parasitemia was occasionally detectable by PCR. Furthermore, initial antibody detection by RAP-1 cELISA in low-dose infected animals was delayed approximately nine and a half days compared to the SBP4 MI-ELISA. Conclusions These results demonstrate excellent diagnostic sensitivity and specificity of the novel SBP4 MI-ELISA for cattle with acute and long-term carrier infections. It is posited that use of this assay in countries that haveB. bovis -endemic herds may be pivotal in preventing the spread of this disease to non-endemic herds.